Analisis Pelaksanaan Peraturan Daerah Berbasis Syariah Provinsi Aceh dalam Perspektif Hak Asasi Manusia - Dessy Marliani Listianingsih (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractThe issuance of Law No. 18/2001 gave the authority for the Aceh Regional Government to exercise special autonomy. The presence of this law also confirms the authority of the Aceh Regional Government to make regional regulations, establish policies, conduct supervision, and foster the administration of governance in Aceh based on Islamic law. However, the administration of government in Aceh as a special autonomy from special regions does not always work well. One that still reaps the pros and cons is the issue of sharia-based regional regulations made and enforced in Aceh. The various regional regulations that have sprung up in Aceh are seen as not paying enough attention to aspects of human rights. Some of them include regional regulations on prohibition of piggybacking between men and women, restrictions on curfew hours, separation of public space between men and women. The latest is the emergence of a circular in the form of an appeal about the standardization of coffee shops, cafes, and restaurants that must be in accordance with Islamic law. This study uses a descriptive qualitative analysis method with a literature review approach. The results of the study stated that the application of regional regulations in Aceh is still a polemic and is reaping the pros and cons in the community.Keywords: Sharia, Local Regulations, Human Rights, Aceh, Discrimination